Biodiesel production from Argemone mexicana oil using chicken eggshell derived CaO catalyst. (15th January 2023) - Ashine, Fekadu; Kiflie, Zebene; Prabhu, Sundramurthy Venkatesa; Tizazu, Belachew Zegale; Varadharajan, Venkatramanan; Rajasimman, Manivasagan; Joo, Sang-Woo; Vasseghian, Yasser; Jayakumar, Mani
Graphical abstract: Highlights: Optimized process was developed for the enhancement of biodiesel production from Argemone Mexicana oil. Improved calcium oxide catalyst was derived from wasted chicken eggshells. Interaction among the selected parameters on the biodiesel yield was investigated through RSM. The optimal condition was compared and ensured by not-statistical techniques, ANN and GA. The obtained AMO biodiesel conversion was analyzed by 1H NMR and FT-IR techniques and physicochemical and fuel properties of AMO biodiesel was studied. Abstract: The present study aimed to optimize the process on the yield percentage of biodiesel from Argemone mexicana oil using calcium oxide as catalyst derived from chicken eggshells. The catalyst was characterized by different techniques, such as X-ray diffraction analysis, Brunauer-Emmett-Teller method with the Barret-Joyner-Halenda model, Fourier transform infrared (FT-IR) spectroscopy, thermogravimetric analysis, and scanning electron microscopy with energy dispersive X-ray studies. The parameters, methanol to oil molar ratio, catalyst loading, and reaction time were optimized through response to surface methodology, which suggested that the improved oil yield was achieved at the molar ratio of methanol to oil: 9.7:1, catalyst loading of 3.05 wt%, and reaction time of 3.01 h for achieving the 99.07 % yield. Further, the optimal values were analyzed by non-statistical techniques, genetic algorithm, and artificial neural network. The acquired biodiesel was characterized by FTIR and 1 H NMR techniques. The reusability of prepared catalyst showed a significant stability for more than 4 times.